Analysis of cadmium (Cd) and lead (Pb) concentration in the blood of street children in high traffic areas of Makassar City, Eastern Indonesia - Mallongi, Anwar; Deka Yana, Arlitha; Jafar, Nurhaeda; Zulkifli, Andi; Daud, Anwar; Syam, Aminuddin; Juliaty, Aidah; Darmo, Kasmuddin; Ka'bah; Asnawi, Amirah (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Air pollution in urban high-traffic areas contributes to exposure to heavy metals, such as cadmium (Cd) and lead (Pb), posing health risks to vulnerable populations, particularly street children. This study aimed to assess the relationship between Cd and Pb concentrations in ambient air and their levels in the blood of street children in Makassar City, Eastern Indonesia, and to evaluate the influence of age and sex.Methods: A cross-sectional study was conducted on 80 street children aged 3–12 years living within 700 m of six high-traffic sites. Ambient air samples were collected using a high-volume sampler and analyzed by Atomic Absorption Spectrophotometry, while blood samples were examined using Inductively Coupled Plasma Mass Spectrometry.Results: The mean blood Pb concentration was 0.32 ng/mL (range 0.05–0.87 ng/mL), which is below the WHO reference threshold of 5 µg/dL, although approximately 10% of the children exceeded this level. The mean blood Cd concentration was 0.68 ng/mL (range 0.12–1.23 ng/mL), which is close to or slightly above the WHO recommended threshold of 1 µg/L in some participants, indicating potential health concern.. The correlation between ambient and blood Pb levels was very weak (r = 0.041; 95% CI: –0.180 to 0.258), and the correlation between ambient and blood Cd levels was weak and imprecise (r = –0.172; 95% CI: –0.377 to 0.050). A moderate negative correlation was observed between age and blood Cd (r = –0.460; 95% CI: –0.617 to –0.267), indicating higher Cd accumulation in younger children than in older children. Sex had little effect on blood Cd and Pb levels.Discussion: These findings highlight that multiple exposure pathways, beyond ambient air, contribute to the heavy metal body burden among street children. Public health interventions addressing environmental sources, nutritional support, and healthcare access are essential to reduce the risk of chronic Cd and Pb exposure in this vulnerable group.